Impact of leukoaraiosis in patients with acute ischemic stroke treated with thrombectomy: a post hoc analysis of the DIRECT-MT trial. (31st January 2022) - Yi, Tingyu; Zhang, Yongxin; Chen, Wen-huo; Wu, Yan-min; Lin, Ding-lai; Lin, Xiao-hui; Zhang, Lei; Xing, Peng-fei; Li, Tianxiao; Zhang, Yongwei; Wang, Shouchun; Yang, Pengfei; et al.
Abstract : Background: The influence of leukoaraiosis in patients with acute ischemic stroke (AIS) given intra-arterial treatment (IAT) with or without preceding intravenous thrombolysis (IVT) remains unknown. Objective: To assess the clinical and radiological outcomes of IAT in patients with or without leukoaraiosis. Methods: Patients of the direct mechanical thrombectomy trial (DIRECT-MT) whose leukoaraiosis grade could be assessed were included. DIRECT-MT was a randomized clinical trial performed in China to assess the effect of direct IAT compared with intravenous thrombolysis plus IAT. We employed the Age-Related White Matter Changes Scale for grading leukoaraiosis (ARWMC, 0 indicates no leukoaraiosis, 1–2 indicates mild-to-moderate leukoaraiosis, and 3 indicates severe leukoaraiosis) based on brain CT. The primary outcome was the score on the modified Rankin Scale (mRS) assessed at 90 days. Results: There were 656 patients in the trial, 649 patients who were included, with 432 patients without leukoaraiosis, and 217 (33.4%) patients with leukoaraiosis divided into mild-to-moderate (n=139) and severe groups (n=78). Leukoaraiosis was a predictor of a worse mRS score (adjusted OR (aOR)=0.7 (95% CI 0.5 to 0.8)) and higher mortality (aOR=1.4 (1.1 to 1.9)), but it was not associated with symptomatic intracranial hemorrhage (sICH) (aOR=0.9 (0.5 to 1.5)). IVT preceding IAT did not increase sICH risk for patients with no (aOR=1.4 (0.6 to 3.4)), mild-to-moderate (aOR=1.5 (0.3 to 7.8)), or severe (aOR=1.5 (0.1 to 21.3)) leukoaraiosis. Conclusion: Patients with leukoaraiosis with AIS due to large vessel occlusion are at increased risk of a poor functional outcome after IAT but demonstrate similar sICH rates, and IVT preceding IAT does not increase the risk of sICH in Chinese patients with leukoaraiosis.